Mixed Farming and its impact on Farm Income; A study in District Faisalabad, Punjab Pakistan - Shahbaz, Pomi; Boz, Ismet; ul Haq, Shamsheer; Khalid, Umer Bin (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
This study was designed to access the impact of mixed farming on farm income of farmers. Other factors influencing the farm income were also planned to study. Total 120 randomly selected farmers interviewed directly. The double log multiple regression analysis was used to study the effect of mixed farming and some other variables on farm income. About 18 percent farmers were only cropped producers, 16 percent farmers were involved in cattle rearing and 65 percent farmers adopted mixed farming. The farm size, No. of animals, crop intensity, cost related to crops and dairy and mixed farming had a positive effect on farm income. The crop sector contributed US 2568.23, dairy sector US 3083.40 and mixed farming (Crop and Livestock) US 13024.71. The cropping intensity provided more options to farmers for resource allocation. The significant effect of mixed farming on farm income was assessed. Mixed farming system was a better option than the single activity as it generates more income